Real-world evidence study on the early use of cemiplimab in the UK: REACT-CEMI (Real World evidence of advanced CSCC treatment with cemiplimab) - Challapalli, Amarnath; Stewart, Grant; Shaw, Heather; Davies, Peter John; Lopez-Baez, Juan Carlos; Ottley, Edward C.; Kelly, Stephen (Frontiers in Immunology, 2024)
Background Cemiplimab was licensed in the United Kingdom (UK) in 2019 for the treatment of patients with locally advanced and metastatic CSCC not suitable for curative surgery or radiotherapy (advanced CSCC [aCSCC]). No UK multi-center studies have investigated the real-world experience of cemiplimab post marketing authorization in aCSCC. Methods This non-interventional retrospective study (10 UK centers) involved data collection from medical records of patients with aCSCC who initiated cemiplimab treatment between 2 July 2019 and 30 November 2020. The study period was a minimum of 12 and a maximum of 36 months post cemiplimab initiation. The primary objective was to describe the real-world clinical effectiveness of cemiplimab (primary outcome: overall response rate [ORR]). Results Of 105 patients, 70% (n=73/105) were male (median [range] age at index of 78.5 [55.4–93.2] years); most patients (63% [n=50/80]) had an Eastern Cooperative Oncology Group (ECOG) score of 1 and 62% (n=63/102) had metastatic disease. The ORR within 12 months was 42% (95% confidence interval [CI] 32%–51%) and the disease control rate was 62% (n=65/105). The median (95% CI) real-world progression-free survival and overall survival from index was 8.6 (6.0–18.7) and 21.0 (14.7–25.2) months, respectively. The median (range) number of cemiplimab infusions was 11.0 (1.0–44.0). Eighty-seven percent experienced no cemiplimab treatment interruptions; 13% (n=14/105) interrupted treatment due to immune-related adverse reactions (irARs) (47% [n=9/19] of treatment interruption events). Eighty-five percent (n=89/105) of patients had discontinued cemiplimab treatment by the end of the study; where reasons for discontinuation were recorded, 20% (n=17/87) discontinued due to the completion of their 2-year treatment course. Nineteen percent (n=20/105) of patients experienced irARs. Conclusion Effectiveness and safety data in this study are broadly similar to previous real-world studies of cemiplimab and the EMPOWER-CSCC1 clinical trial; with our cohort representing a broader population (included immunocompromised and transplant patients). Results support the use of cemiplimab for the treatment of aCSCC in a real-world setting.